Efektivitas Disiplin Kerja Dalam Meningkatkan Kinerja Aparatur Sipil Negara Pada Biro Umum Setda Provinsi Sulawesi Tenggara - Tahmit Ansar (Jayapangus Press, 2018)
This study aims to analyze the effectiveness of Work Discipline in Improving the Performance of State Civil Apparatus on the General Bureau of Southeast Sulawesi Regional Sekretariat, with indikators of disciplinary assessment: time discipline, rules and responsibilities and performance appraisal indikators consist of: work achievement, and work performance. This study took a sample of 2 people, consisting of Head of Public Bureau and Head of Administration. The results of research show that the effectiveness of Work Discipline in Improving Performance of State Civil Apparatus At Public Bureau of Regional Sekretariat of Southeast Sulawesi has been done well. This is seen in the indikator of work discipline has the highest score (60.00%) ,, on the level of effectiveness of work indicates that the indikator of achievement of work shows the score (73.33%), so the Effectiveness of Work Discipline in Improving Performance of Civil State Apparatus On Bureau General Sekretariat of Southeast Sulawesi Province can be said to have done well.